Effect of the incorporation of polyols, fructooligosaccharides and antihypertensive peptides in a deposited marshmallow - Sánchez Orozco, Mike Douglas; Gomez Daza, Juan Carlos; Giraldo, Carlos Julian (Revista Colombiana de Investigaciones Agroindustriales, 2022)
Traditional marshmallows are made with sucrose and glucose syrup; an option for making healthy, sucrose-free marshmallows with functional components is the use of polyols, fructo oligosaccharides (FOS) and antihypertensive peptides. The objective of this research was to evaluate the effect of the inclusion of Nutraflora® (FOS), maltitol (M), sorbitol syrup (JS) and antihypertensive peptides in a marshmallow on the elastic modulus (EM) of the prototypes produced. A 3x2² factorial arrangement (FA) was proposed to evaluate the effects of the proportions of polyols - FOS, gelatin and antihypertensive peptides on the EM of the prototypes, followed by a completely randomized design (CRD) to compare a control masmelo and an extreme vertex mixture design (EVMD) to optimize the formulation. Finally, the texture profile (TPA) of the developed masmelo was determined. The proportions of polyols in the FA and DCA caused effect on the ME (p<0.05). The DMVE determined the corresponding proportions of 8.45% FOS; 46.55% M and 25% JS. The regression model obtained an r² = 93.60, r² (adjusted) = 90.40 and r² (predicted) = 80.03.